2022
DOI: 10.3389/fspas.2022.864294
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Physics Constraints at Different Densities to Probe Nuclear Symmetry Energy in Hyperonic Neutron Stars

Abstract: The appearance of strangeness in the form of hyperons within the inner core of neutron stars is expected to affect its detectable properties, such as its global structure or gravitational wave emission. This work explores the parameter space of hyperonic stars within the framework of the Relativistic Mean Field model allowed by the present uncertainties in the state-of-the-art nuclear and hypernuclear experimental data. We impose multi-physics constraints at different density regimes to restrict the parameter … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 101 publications
1
17
0
1
Order By: Relevance
“…However, the parameter is fixed such that the EoS should able to reproduce the maximum observed neutron star mass. In many works the vector self interaction is either ignored [16,18,19,31] or they are fixed to constant value [15,32] by choosing a particular EoS model. In this work we will consider the variation of all nuclear saturation parameters along with and the ranges for each of the variables are provided in Table 1.…”
Section: Microscopic Eos Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the parameter is fixed such that the EoS should able to reproduce the maximum observed neutron star mass. In many works the vector self interaction is either ignored [16,18,19,31] or they are fixed to constant value [15,32] by choosing a particular EoS model. In this work we will consider the variation of all nuclear saturation parameters along with and the ranges for each of the variables are provided in Table 1.…”
Section: Microscopic Eos Modelmentioning
confidence: 99%
“…By applying the maximum mass constraint resulting from the observed massive pulsar, one can limit the allowed range for . Other physical constraints considered in different works include the constraints following chiral effective field theory ( EFT), which describes the behaviour of low-density nuclear matter (0.5-1.4 0 ) [44,45,46,18,19,47,48]. At such low densities, nuclear matter is insensitive to [35].…”
Section: Maximum Neutron Star Mass and -Meson Self Interaction Streng...mentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous work (Ghosh et al 2022a), it was explicitly demonstrated that including the statistical re-weighting using χ-squared statistics might change the posterior probability distribution slightly, but it does not significantly alter the physical correlation between nuclear empirical parameters and astrophysical observables. Many other works have followed the same scheme (Kurkela et al 2014;Most et al 2018;Annala et al 2018;Annala et al 2020;Ghosh et al 2022b). A similar scheme was employed to study the correlations between nuclear parameters in various works (Chatterjee et al 2017;Margueron et al 2018;Ghosh et al 2022a,b).…”
Section: Cut-off Filter Schemementioning
confidence: 99%